"The more I do, the more I can do": perspectives on how performing daily activities and occupations influences recovery after surgical repair of a distal radius fracture. Issue 19 (11th September 2022) - Collis, Julie M.; Mayland, Elizabeth C.; Wright-St Clair, Valerie; Signal, Nada
Abstract: Purpose: The study aimed to explore perceptions and experiences about how engaging in daily activities and occupations influenced recovery in the first eight weeks after surgical treatment of a distal radius fracture. Methods: Twenty-one adults completed an online activity and exercise log then participated in a semi-structured interview between weeks 6 and 8 postoperatively. Interviews were transcribed and analysed using reflexive thematic analysis. Results: Daily activities and occupations were highly influential in facilitating recovery of movement and function of the operated limb. Five themes provided an understanding of how occupation operated to promote recovery. Occupation was (i) a primary driver of the rehabilitative process, providing an impetus for recovery, (ii) offered ready-to-hand challenges for opportunistic, automatic movement, (iii) invited intentional use of the affected wrist, (iv) habituated the wrist to movement through repetition and confidence-building, and (iv) drew on psychosocial resources to enable reengagement with life activities and roles. Conclusions: Incorporating the performance of graded, modified activities during the early weeks of rehabilitation creates opportunities for wrist movement, enhances wellbeing, and assists in the habituation of wrist movement. Activities and occupations can be used as a therapeutic strategy to promote recovery from surgical treatment of a distal radius fracture. Implications for rehabilitation: Rehabilitation after surgical repair of distal radius fractures has traditionally focused on exercise routines. Daily activities and occupations can also be used to promote wrist movement and function during the early weeks of rehabilitation. Occupation is a naturally occurring source of wrist movement, motivation, and wellbeing that can be harnessed for therapeutic advantage after surgical repair of distal radius fractures. Therapists can collaborate with patients to select and modify daily activities and occupations to incorporate into early postoperative therapy programmes.